South Korea Tourism Advertising Semiotics Seoul X BTS Version - Nadia Oktaviani; Regita Ariana Ramadhani; Yenny Pingky Krisnawati Chia (Budapest International Research and Critics University, 2022)
The Corona Virus pandemic has devastated the tourism industry worldwide, including South Korea, which has suffered a significant decline in international tourists. This has prompted the South Korea Government to create tourism advertisements on YouTube featuring one of South Korea's most famous K-Pop idols, Bangtan Sonyeondan (BTS), in a tourism advertisement named [SEOUL X BTS] SEE YOU IN SEOUL with the intention of increasing the foreign visitors who regard BTS as K-Pop idols. This was conducted through a collaboration between the South Korean government and the KTO, the country's agency for the creative industry. This research aimed to identify and analyze how the South Korean government constructs commercial diplomacy through the South Korean tourism advertisement [SEOUL X BTS] SEE YOU IN SEOUL version. This study utilized a qualitative method supported by Roland Barthes' semiotic theory to delve deeper into the message of denotation, connotation, and myth meaning in tourism advertisements as an attempt to promote and introduce South Korean tourism. Additionally, a theoretical approach focusing on mass media was used, particularly advertising. Based on the results of the study, the tourism advertisement titled [SEOUL X BTS] SEE YOU IN SEOUL includes two types of markers: first, audio-visual markers that can be seen and heard, and second, in the form of body gestures, sounds, and expressions. Thrid denotative meanings from the advertisement suggest a tourist who is disappointed that he/she was unable to travel abroad because something significant has occurred in the world, leading to the shutting down of all access to travel the world. fourth connotative meanings illustrate how humans have always coexisted in an uncertain world filled with fear and worry.